TATA KELOLA REKAM MEDIS BERBASIS ELEKTRONIK DALAM PENGELOLAAN LAPORAN PASIEN RAWAT INAP BPJS KESEHATAN MENGGUNAKAN MICROSOFT VISUAL STUDIO - Wahyudin; Edi Suharto; Erix Gunawan (Jurnal Infokes, 2023)
In medical records, patient report management is very important for hospitals in collecting data if there are new or old patients who have been treated will make it easier to find patient data. The Medical Recorder section in charge will carry out the data processing process by inputting user data, doctor data, diagnosis data, visit type data and polyclinic type data. Furthermore, the medical recorder, namely the reporting section, will get the information to be used as material for making patient data reports, BPJS Health inpatient visit reports. In the process of making reports of BPJS health inpatients at hospitals, there are still shortcomings. The obstacle in the process of making BPJS health inpatient reports is that the medical record file has not been filled in completely so that work becomes hampered and there are often delays in submitting reports. The purpose of this study is to design an electronic-based medical record information system in making BPJS health inpatient reports at hospitals. In this discussion, the research used is using qualitative methods in a descriptive approach. In collecting problems, the authors used observation methods and interviews with medical record officers. Inpatient reporting officers are the subject of research while BPJS health inpatient data is the object of research. The result of this study is the design of an information system for reporting inpatients of BPJS health at hospital. Keywords: Report, Medical Record, Hospitalization, BPJS Health